Cost Analysis of Antihypertensive Therapy in the Hypertensive Patients - Paudel, Sabita; Adhikari, Sudeshana; Upadhyaya, Tirtha Lal; Subedi, Nuwadatta (Journal of College of Medical Sciences-Nepal, 2024)
Background Hypertension is an established chronic disease with a huge economic burden to society so choosing cost effective medication is essential. Several medications are available and the decision lies in the prescriber so the generation of evidence suggesting cost-effective medication is essential. The objective of the study was to explore cost effective treatment of hypertension. Methods A descriptive cross-sectional study was carried out among hypertensive patients of 20-69 years of age taking antihypertensive medicines for more than one year. Four commonly prescribed drug groups were included: calcium channel blocker, angiotensin receptor blocker, diuretics plus calcium channel blocker, and angiotensin receptor blocker plus calcium channel blocker. The direct medical cost, direct non-medical cost and overall cost of each class of antihypertensive medicine group was estimated as the median cost of that class. The cost-effectiveness relationship was described as a ratio of annual median cost to proportion of patients with controlled hypertension for each pharmacological group. Results Angiotensin receptor blocker was the group with lowest annual overall median cost (8915 NPR). Cost effectiveness relationship of calcium channel blocker group was the lowest (10537.83) followed by angiotensin receptor blocker (15115.25) and calcium channel blocker plus angiotensin receptor blocker (21305.69). Conclusions Calcium channel blocker was the most cost effective group of antihypertensive drugs. The direct medical costs accounted for high amount of costs for hypertensive patients in all four groups.